Influence of Occult Hepatitis B Infection on Blood Transfusion Safety and Its Countermeasures - Meng Yi; Shuchang Dai; Lin Fang; Bo Pan; Bin Fan; Yiming Pan; Zhong Liu (Pathogens)
Occult hepatitis B infection (OBI) is a serious public health issue. Although a number of effective hepatitis B vaccines are available, hepatitis B still poses a threat to global public health. Patients with OBI are usually asymptomatic, but there may be active HBV DNA present in their blood, leading to the risk of virus transmission during blood transfusions or organ transplantation, constituting a hazard to the health of recipients and increasing the risk of liver cirrhosis and liver cancer. Although China has progressed in the development of blood-screening technology, OBI is still a significant hidden danger to blood transfusion safety. Therefore, in blood screening and blood transfusion, strengthening the monitoring and management of OBI is crucial to ensure blood safety and protect public health.